The university goes to the field: report on the participatory construction of a memory space of minas artesanal cheese from Campo das Vertentes, Minas Gerais State, Brazil (Research, Society and Development, 2020)
This article is part of the master’s thesis of the Interdepartmental Program of Post-graduate Program in Arts, Urbanities and Sustainability of the Federal University of São João del Rei/MG. The objective was to understand the perception of the producers of artisanal Minas cheese producers from Campo das Vertentes / MG in relation to their own activity, having as its north the analysis of their daily poetics and the rescue of their memories. It also sought to reconcile science and art, inspiring participation, the exchange of knowledge, and strengthening collective identity through the construction of a place of memory. This study has extensionist character, qualitative and linked to research-action. In addition to a bibliographic review, interviews and a photographic experience were conducted that recorded the daily expressions of the activity generating a visual and identity narrative of this group of people, corroborating for the construction of a space of identity and memory of this activity. It was possible to conclude that contemporary influences interfere directly on the daily life of these producers, leading them to break paradigms in search of maximization of results and facilitation of daily routines. In this sense, the current market pattern imposes on these producers the dissemination of new social behaviors and a process of cultural homogenization.